Cardiovascular Surveys in Areas with Different Water Supplies. Issue 5758 (15th May 1971) - Elwood, P. C.; Bainton, D.; Moore, F.; Davies, D. F.; Wakley, E. J.; Langman, M.; Sweetnam, P.
Abstract : Cardiovascular surveys were conducted in areas with different water supplies. In two areas with hard water 243 men were seen and in three areas with soft water 357 men were seen. There was no evidence of an important difference between the two areas in blood pressure, serum cholesterol, blood sugar, or packed cell volume. A variety of measurements were made on an E.C.G. The P-R interval was significantly longer in the men in the hard water area, and a 40-complex trace showed ventricular extrasystoles in a significantly higher proportion of these men than in those in the soft water area.